2016
DOI: 10.1016/j.scitotenv.2016.06.174
|View full text |Cite
|
Sign up to set email alerts
|

Ecological response to hydrological variability and catchment development: Insights from a shallow oxbow lake in Lower Mississippi Valley, Arkansas

Abstract: The ecological response of shallow oxbow lakes to variability in hydrology and catchment development in large river floodplain ecosystems (RFE) in Arkansas remains largely unknown. Investigating these responses will advance our understanding of ecological evolution of oxbow lakes in response to the major environmental drivers, which will establish baseline conditions required to develop effective management practices for RFE. In this pilot study, we examined the potential of using a dated surface sediment core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Prior work by Randsalu-Wendrup et al (2014 demonstrated that these alternative states-and shifts between them-can be inferred using diatom assemblages in sedimentary records because diatom taxa can be classified as planktonic or epiphytic. Similar state changes have been inferred using diatom records from shallow lakes, which show shifts from epiphytic to planktonic taxa in response to more eutrophic conditions, as aquatic macrophytes are replaced by planktonic algae in response to an increase in nutrient delivery to the lake (Bhattacharya et al 2016;Sayer et al 2010). At Horseshoe Lake, we interpret the prominent shift in diatom assemblages in the 14th century as a shift from a eutrophic to more mesotrophic state when prehistoric populations abandoned the area and nutrient inputs to the lake from settlements and agricultural fields in the watershed declined.…”
Section: Diatom Assemblages Associated With Prehistoric Human Populatsupporting
confidence: 69%
See 2 more Smart Citations
“…Prior work by Randsalu-Wendrup et al (2014 demonstrated that these alternative states-and shifts between them-can be inferred using diatom assemblages in sedimentary records because diatom taxa can be classified as planktonic or epiphytic. Similar state changes have been inferred using diatom records from shallow lakes, which show shifts from epiphytic to planktonic taxa in response to more eutrophic conditions, as aquatic macrophytes are replaced by planktonic algae in response to an increase in nutrient delivery to the lake (Bhattacharya et al 2016;Sayer et al 2010). At Horseshoe Lake, we interpret the prominent shift in diatom assemblages in the 14th century as a shift from a eutrophic to more mesotrophic state when prehistoric populations abandoned the area and nutrient inputs to the lake from settlements and agricultural fields in the watershed declined.…”
Section: Diatom Assemblages Associated With Prehistoric Human Populatsupporting
confidence: 69%
“…Sediments, diatoms, and other materials deposited in oxbow lakes are sourced from the lake itself (autochthonous) or its watershed (allochthonous), but during flood stages the main river channel may also deposit material in the lake (Toonen et al 2012;Bhattacharya et al 2016), which represents an extralocal source of allochthonous material. In a previous study of Horseshoe Lake's sedimentary record, Munoz et al (2015) used grain-size analysis to identify the timing of major overbank flood events of the Mississippi River (Fig.…”
Section: Diatoms In Floodplain Lakesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, small centric diatom species, such as D. stelligera , are also responsive to changes in nutrient availability, and an increased N:P ratio (Saros & Anderson, ). Moreover, Bhattacharya, Hausmann, Hubeny, Gell, and Black () link abundant Aulacoseira granulata , along with Cyclotella meneghiniana and Discostella spp., with nutrient‐enriched, turbid conditions in a Lower Mississippi floodplain lake in Arkansas, U.S.A. Thus, the co‐occurrence of relatively abundant A. granulata , C. meneghiniana and Discostella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms are diverse and sensitive to a range of environmental factors, including water quality, hydrological conditions and trophic state, and their assemblages in sediments have been used to establish past ecological conditions in many shallow lakes (Bhattacharya, Hausmann, Hubeny, Gell, & Black, ; Wu et al., ). The abundance of epiphytic diatoms generally increases with the abundance of aquatic macrophytes and they are considered to be a useful indicator of changes in macrophyte abundance (Karst & Smol, ; Yang, Shen, Dong, Liu, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%